IMPLEMENTASI KEBIJAKAN PEMBINAAN ANAK JALANAN, GELANDANGAN, PENGEMIS DAN PENGAMEN DI KOTA MAKASSAR PROVINSI SULAWESI SELATAN - Endang Sri Hidayah (Fakultas Politik Pemerintahan IPDN, 2020)
Makassar City is a city that has various complex problems, including the existence of homeless youth, homelessness, beggars and Busker or street musicians. City development has become an attraction for the outside community so that it has an impact on the flow of urbanization, the population is increasing and it is difficult to find work in the city. This study aims to describe how the implementation of the Makassar City Regulation Number 2 of 2008 concerning Development of homeless youth, homelessness, beggars and Busker or street musicians, as well as to find out what strategies the Makassar City Government has implemented in dealing with homeless youth, homelessness, beggars and Busker or street musicians. The analysis conducted by researchers is using the theory of implementation of Van Meter and Van Horn with qualitative descriptive research methods with an inductive approach. To analyze the strategy, the researcher used a SWOT analysis to provide an alternative strategy. From the research results, it is concluded that the coaching has not been successful, there are still measures and policy objectives that have not been achieved, additional funding resources are needed for employees who go to the field every day, the characteristics of the implementing agencies in implementing this policy are adjusted to the objects found in the field. , although communication between organizations between Dinsos in collaboration with the Satpol PP, YKP2N and rehabilitation centers has been carried out quite well, the economic, social and political environment of the community has not played an active role in helping the City Government implement this policy. There are still many people with social illnesses who have been coached back to the streets, the attitude of the implementers has the principle of integrity coordination and synchronization both vertically and horizontally, although in practice it has not been carried out optimally. Based on the identification results of internal factors and external factors in the SWOT analysis, 9 (nine) strategic issues were generated.Keywords: implementation, policy, coaching, homelessness, city of Makassar.